Теоретичні й експериментальні дослідження нестаціонарних процесів у механічній системі пасажирського ліфта - Бондарчук, Богдан (КІНПАТРІ ЛТД, 2013)
The results of experimental researches of transient modes of the passenger elevator are considered. There are investigated the influence of load mass and length of rope branch by which the motion is transmitted from the driving pulley to the cabin on the dynamic efforts in the rope. The comparative analyses of the results of theoretical and experimental studies are carried out.
The theoretical and experimental researches of nonstationary processes in passenger elevators mechanical systems